PRELIMINARY SURVEY ON THE VERMETID REEFS ALONG THE APULIAN COAST IN THE PROVINCE OF BRINDISI - Coccia, Isabella; Marra, Manuel; Luce, Gaetano; Oddenino, Muriel; Lazic, Tamara; Gravina, Maria Flavia; Mercurio, Maria (Biologia Marina Mediterranea, 2024)
This study describes for the first time vermetid platforms along the Adriatic coast of Apulia, in the province of Brindisi. The study has been carried out on the coastline between Savelletri and “Lamaforca” for approximately 24.5 linear km, identifying two types of habitus: encrusting (<1 cm thick) and reef (>1 cm thick). In the first 7 kilometres of coastline, bioconstructions were almost absent, while they were more concentrated on the coastline between Torre Canne and Villanova; platforms were also present on the coastline between Villanova and “Lamaforca”, although in smaller quantities. Morphological investigations confirmed that the bioconstructor species was Dendropoma cristatum (Biondi, 1859); data on the density of individuals and the size of opercula were in line with data from studies carried out in the rest of the Mediterranean Sea; the associated fauna was instead modest. The main anthropogenic impact observed was the trampling. These data represent the first detailed study on vermetid platforms in Apulia, but further studies are needed to describe these platforms also along the Ionian coast.